A New Clue for the Late Eocene Freshwater Ecosystem of Central China Evidenced by New Fossils of Trapa L. and Hemitrapa Miki (Lythraceae) - Zhuochen Han; Hui Jia; Xiangning Meng; David K. Ferguson; Mingyue Luo; Ping Liu; Junjie Wang; Cheng Quan (Biology, 2022)
Both Trapa L. and the extinct Hemitrapa Miki are aquatic plants in the family Lythraceae, with abundant fossil records in Eurasia and North America in the Cenozoic. However, documented materials are mainly based on fruit and pollen grains without reliable leaf fossils. Here, we report fossil leaves, fruit, and roots of Trapa and fruit of Hemitrapa from the late Eocene of Weinan, the Weihe Basin of central China. The fossil leaves are identified as a new species, Trapa natanifolia Z. C. Han et H. Jia sp. nov., which represents the earliest known record of a Trapa leaf fossil. It is remarkably similar to extant species of Trapa, mostly due to the unique inflated petiole structures found in both of them. While displaying prominent intergeneric differences, the incomplete fossil fruits are assigned to Trapa sp. indet. and Hemitrapa sp. indet. The former is the earliest fossil fruit record of Trapa, and the latter represents the earliest fossil record of Hemitrapa found in Asia. These new fossil discoveries suggest that the divergence of Trapa and Hemitrapa occurred at least by the late Eocene. It is believed that modern Trapa most likely originated in China. Furthermore, this unexpected aquatic plant fossil assemblage indicates that central China was warm and humid, with freshwater ponds or lakes, in the late Eocene and not as arid as previously thought.